Exploiting of green synthesized silver nanoparticles using Capparis spinosa L. Fruit for spectrophotometric determination of diphenhydramine HCl in pure forms and commercial products - Fadam M. Abdoon; Hasan M. Hasan; Sarhan A. Salman; Suham T. Ameen; Mequanint Birhan (Journal of Experimental Nanoscience)
A novel, sensitive, economical, and environmentally friendly method is described for the quantitative determination of diphenhydramine hydrochloride (DPH). The method is based on the preparation of silver nanoparticles (AgNPs) from the extract of Capparis spinosa L. (CPL) fruits to determine DPH as one of the antihistamine drugs. The colour intensity of the solution increases with increasing DPH concentrations due to the interaction of AgNPs with DPH. FTIR, X-ray, EDX, SEM, and UV-Vis techniques characterised the prepared nanoparticles. The current method presented a linear relationship over the concentration range of 2–45 µg/mL at a wavelength of 415 nm. The detection limit (LOD) and quantitation limit(LOQ) are studied, and the values ​​are 0.36 and 1.19 µg/mL, respectively. The recovery percentage (accuracy function) is more than 99.5%, and the relative standard deviation (RSD%, as a precision function) was 0.73%. The molar absorptivity and Sandel’s sensitivity index are 5.14 × 103 L.mol−1.cm−1 and 0.057 µg.cm−2, respectively. The data were compared to those from other previous approaches using t-test and F-test with a 95% confidence level and found to be 2.107 and 3.18, respectively. According to the ICH guidelines (2005), the proposed method has been validated and provides promising results for determination of DPH in pure form and pharmaceutical preparations.